Congenital alveolar rhabdomyosarcoma in a newborn. - Garay, M.; Chernicoff, M.; Moreno, S.; Pizzi de Parra, N.; Oliva, J.; Apréa, G. (European Journal of Pediatric Dermatology, 2004)
We report a neonatal case of congenital alveolar rhabdomyosarcoma, presenting as a purple-red tumor on the left upper eyelid. The patient was treated with partial excision, chemotherapy and, finally, at the age of one year, radiotherapy. He was free of recurrences during 18 months of follow-up.